Mineralization of Nitrogen, Phosphorus and Sulphur in Soil as Influenced by Rock Phosphate Enriched Compost and Chemical Fertilizers - and S.C. Datta, P.C. Moharana, D.R. Biswas (Journal of the Indian Society of Soil Science, 2015)
Quantitative information on nutrient mineralization in soil under different nutrient management strategies is essential for better assessment of nutrient availability and their loss from soil. Predicting nutrient mineralization has been one of the greatest challenges to improve nutrient management in agriculture. Laboratory incubation experiment was conducted to study the nitrogen (N), phosphorus (P) and sulphur (S) mineralization in soils amended with rock phosphate (RP) enriched composts and fertilizers over 120 days. Results revealed that RP enriched compost amended soil mineralized higher N and S over unfertilized control. The first-order model was found to be the best suitable for N and S mineralization because it provided the best fit to the experimental data and for its simplicity. Potentially mineralized N (N0) values ranged from a minimum of 4.0 mg kg-1 to a maximum of 52.1 mg kg-1 soil and the mineralization rate k varied from 0.023 to 0.052 day-1. It was observed that model fitting for P mineralization did not yield satisfactory results for soil amended with RP enriched compost. The P mineralization study revealed that the soil treated with RP enriched compost showed decline in Olsen-P during the initial stages of 30 days, but improved significantly with the progress of time, indicating that RP enriched compost released P for a longer period which in turn could steadily supply nutrients for longer period for crop growth. The RP enriched compost substantially increased the amount of potentially mineralizable S (S0) and higher rates of S mineralization (k) over unfertilized control.